Reassessing Employee Involvement And Participation: Atrophy, Reinvigoration And Patchwork in Australian Workplaces - Wilkinson, A.; Townsend, K.; Burgess, John (Sage Journals, 2013)
Within Australia and internationally, much of the research on employee involvement and participation developed historically with a focus on the role of unions in ensuring employees had the opportunity to play a role in decision-making at the workplace, organisation or industry level. Partly in response to changing union fortunes and their lesser centrality to employment relations in many countries, and partly as an acknowledgement to the hitherto inadequate conceptualisation of participation, researchers had developed more nuanced themes to the body of work on employee involvement and participation, for example, formalised non-union participation, informal participation and multiple channels. By adapting and extending a model of participation and drawing on data from five workplaces, we show that employee involvement and participation is multidimensional and that some elements atrophy while others are reinvigorated, and we find a limited overall strategy and more patchwork to employee involvement and participation architecture in these workplaces. Equally, despite the interest in the ideas of employee involvement and participation and the idea of multiple channels, it does tend to be confined to a limited range of topics, especially information-passing with a hint of consultation, rather than any notion of industrial democracy. The channels are wide rather than deep.